Inflammasome activity is essential for one kidney/deoxycorticosterone acetate/salt‐induced hypertension in mice. (31st July 2015) - Krishnan, S M; Dowling, J K; Ling, Y H; Diep, H; Chan, C T; Ferens, D; Kett, M M; Pinar, A; Samuel, C S; Vinh, A; Arumugam, T V; Hewitson, T D; et al.
Abstract : Background and Purpose: Inflammasomes are multimeric complexes that facilitate caspase‐1‐mediated processing of the pro‐inflammatory cytokines IL‐1β and IL‐18. Clinical hypertension is associated with renal inflammation and elevated circulating levels of IL‐1β and IL‐18. Therefore, we investigated whether hypertension in mice is associated with increased expression and/or activation of the inflammasome in the kidney, and if inhibition of inflammasome activity reduces BP, markers of renal inflammation and fibrosis. Experimental Approach: Wild‐type and inflammasome‐deficient ASC −/− mice were uninephrectomized and received deoxycorticosterone acetate and saline to drink (1K/DOCA/salt). Control mice were uninephrectomized but received a placebo pellet and water. BP was measured by tail cuff; renal expression of inflammasome subunits and inflammatory markers was measured by real‐time PCR and immunoblotting; macrophage and collagen accumulation was assessed by immunohistochemistry. Key Results: 1K/DOCA/salt‐induced hypertension in mice was associated with increased renal mRNA expression of inflammasome subunits NLRP3, ASC and pro‐caspase‐1, and the cytokine, pro‐IL‐1β, as well as protein levels of active caspase‐1 and mature IL‐1β. Following treatment with 1K/DOCA/salt, ASC −/− mice displayed blunted pressor responses and were also protected from increases in renal expression of IL‐6, IL‐17A, CCL2, ICAM‐1 and VCAM‐1, and accumulation of macrophages and collagen. Finally, treatment with a novel inflammasome inhibitor, MCC950, reversed hypertension in 1K/DOCA/salt‐treated mice. Conclusions and Implications: Renal inflammation, fibrosis and elevated BP induced by 1K/DOCA/salt treatment are dependent on inflammasome activity, highlighting the inflammasome/IL‐1β pathway as a potential therapeutic target in hypertension. Linked Articles: This article is part of a themed section on Inflammation: maladies, models, mechanisms and molecules. To view the other articles in this section visithttp://dx.doi.org/10.1111/bph.2016.173.issue-4